Properties, Preparation, and Application of Magnesium - Sayyed Abdul Halim Tawana; Shafiullah Arghandiwal (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
This article reviews comprehensively the chemistry of magnesium, its properties, preparation and applications in various fields. Starting with an overview of its characteristics; chemical and physical to the metal’s discovery through the ages with electrochemical and thermal routes to the modern large-scale production processes. Magnesium’s sources, alongside conventional mining and concentration techniques for magnesite, dolomite, carnallite, and marine brines are disscussed. Extraction technics; electrolysis and thermal reduction are presented. Then, the article explores magnesium and its alloys principal applications: its metallurgical, electrochemical, pyrotechniques and its compounds application. By combining historical context, processing chemistry, and end-use performance, this article highlights magnesium’s marvelous importance and brings opportunities for future technological advances.